Bipolar disorder: a review of conceptual and clinical aspects - Bosaipo, Nayanne Beckmann; Borges, Vinícius Ferreira; Juruena, Mario Francisco (Medicina (Ribeirao Preto), 2017)
This review aims to introduce historical, epidemiological and etiological aspects of bipolar disorder, also to present the characterization and course of the disease, as well as some issues related to the diagnosis, treatment and prognosis. Bipolar disorder (BD) is characterized by severe mood disturbances, involving periods of elevated mood and depression intercalated with periods of remission. The disorder is distinguished into two main types: Type I, in which episodes of mania occur; and Type II, in which mood elevation is milder and briefer, characterizing episodes of hypomania. The concept of bipolar spectrum extends the classification of BD, including clinical and genetic patterns. BD is a common disease that strikes about 30 million people worldwide, affecting men and women differently. The causes of BD include the interaction of genetic and environmental factors, distinguishing it as a complex and multidimensional disorder. The diagnosis according to DSM-5 involves the identification of mania or hypomania symptoms and the longitudinal evaluation of the disease course. Depression is usually the most common and persistent condition among bipolar patients. Although there are no specific symptoms that distinguish unipolar depression from bipolar depression, typical clinical features of each manifestation were found (e.g., symptom profile, family history, and disease course). Early diagnosis and the treatment of acute mood episodes significantly improve the prognosis. The first choice treatment involves mood stabilizers, anticonvulsants and atypical antipsychotics. The combination of medication with psychosocial interventions has been proved effective. However, the use of antidepressant monotherapy is not recommended